Improving Healthcare Workers' Adherence to Surgical Safety Checklist: The Impact of a Short Training - Ferorelli, Davide; Benevento, Marcello; Vimercati, Luigi; Spagnolo, Lorenzo; De Maria, Luigi; Caputi, Antonio; Zotti, Fiorenza; Mandarelli, Gabriele; Dell'Erba, Alessandro; Solarino, Biagio (Frontiers in Public Health, 2022)
Background Although surgery is essential in healthcare, a significant number of patients suffer unfair harm while undergoing surgery. Many of these originate from failures in non-technical aspects, especially communication among operators. A surgical safety checklist is a simple tool that helps to reduce surgical adverse events, but even if it is fast to fill out, its compilation is often neglected by the healthcare workers because of unprepared cultural background. The present study aims to value the efficacy of a free intervention, such as a short training about risk management and safety checklist, to improve checklist adherence. Methods In March 2019, the medical and nursing staff of the General Surgical Unit attended a two-lesson theoretical training concerning surgical safety and risk management tools such as the surgical safety checklist. The authors compared the completeness of the surgical checklists after and before the training, considering the same period (2 months) for both groups. Result The surgical safety checklists were present in 198 cases (70.97%) before the intervention and 231 cases (96.25%) after that. After the training, the compilation adherence increased for every different type of healthcare worker of the unit (surgeons, nurses, anesthetists, and scrab nurses). Furthermore, a longer hospitalization was associated with a higher surgical checklist adherence by the operators. Conclusions The results showed that a free and simple intervention, such as a two-lesson training, significantly stimulated the correct use of the surgical safety checklist. Moreover, the checklist adherence increased even for the operators who did not attend the training, maybe because of the positive influence of the colleagues' positive behaviors. As the results were promising with only two theoretical lessons, much more can be done to build a new safety culture in healthcare.